2023
DOI: 10.1002/smll.202207231
|View full text |Cite
|
Sign up to set email alerts
|

Programmable DNA Hydrogel Provides Suitable Microenvironment for Enhancing TSPCS Therapy in Healing of Tendinopathy

Abstract: Tendon stem/progenitor cells (TSPCs) therapy is a promising strategy for enhancing cell matrix and collagen synthesis, and regulating the metabolism of the tendon microenvironment during tendon injury repair. Nevertheless, the barren microenvironment and gliding shear of tendon cause insufficient nutrition supply, damage, and aggregation of injected TSPCs around tendon tissues, which severely hinders their clinical application in tendinopathy. In this study, a TSPCs delivery system is developed by encapsulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…To address this issue, Guanglin Wang et al developed a DNA hydrogel scaffold encapsulating TDSCs. This DNA hydrogel scaffold extends the retention time of TDSCs on the tendon, providing an artificial microenvironment conducive to better nutrition, thereby promoting tendon injury repair ( Ge et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, Guanglin Wang et al developed a DNA hydrogel scaffold encapsulating TDSCs. This DNA hydrogel scaffold extends the retention time of TDSCs on the tendon, providing an artificial microenvironment conducive to better nutrition, thereby promoting tendon injury repair ( Ge et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, to create a suitable niche for the tendon lineage differentiation of TSPCs, such as ECM combined with hydrogel to promote the sustained generation of TSPCs. Ge et al [ 136 ] injected TSPCs-Gel into rat injured Achilles tendons using DNA hydrogel as an excellent artificial ECM for proliferation and protection of TSPCs (TSPCs-Gel). They found that TSPCs-Gel injection not only promoted the healing of rat tendon, but also improved its ultimate loading ability.…”
Section: Discussionmentioning
confidence: 99%
“…Delivery system for tendon stem/progenitor cells Hydrogel promotes cell proliferation and protection [12] 3D printed hydrogel particles containing PRP Tendon postinjury repair Hydrogel promotes tendon differentiation in tendon-derived stem cell and reduces inflammatory response [16] Gelatin/Fe3O4/Celecoxib hydrogel Repair the later stage in tendinopathy Hydrogel reduced inflammatory reaction of macrophage response [19] Chitosan-collagen HG with poly-L-lactide fibers To mimic the glycosaminoglycans of sheath extracellular matrix for tendon regeneration Good cell proliferation was observed, tenocytes showed proper attachment and spreading on the scaffolds, indicating that they would be suitable for flexor tendon regeneration [38] Collagen I hydrogels Bioengineered Tissue microenvironments Scaffolds for engineered tissues with a diffusion capacity [43] Thermo-responsive in-situ HG based on poly (Nisopropylacrylamide)…”
Section: Adn Hydrogelmentioning
confidence: 99%